2022
DOI: 10.1053/j.jvca.2021.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Acute Respiratory Distress Syndrome in the Perioperative Period of Cardiac Surgery: Predictors, Diagnosis, Prognosis, Management Options, and Future Directions

Abstract: Acute respiratory distress syndrome (ARDS) after cardiac surgery is reported with a widely variable incidence (from 0.4%-8.1%). Cardiac surgery patients usually are affected by several comorbidities, and the development of ARDS significantly affects their prognosis. Herein, evidence regarding the current knowledge in the field of ARDS in cardiac surgery is summarized and is followed by a discussion on therapeutic strategies, with consideration of the peculiar aspects of ARDS after cardiac surgery. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 83 publications
(90 reference statements)
0
19
2
1
Order By: Relevance
“…According to relevant studies, the incidence rate of ARDS following cardiac surgery ranges from 0.4 to 8.1% ( 17 , 28 , 36 ). Daryl et al reported a 2.6% (113/4,366) incidence of ALI and ARDS in patients undergoing high-risk surgery, and 3.3% and 22% for patients undergoing spine surgery and high-risk vascular surgery, respectively ( 17 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to relevant studies, the incidence rate of ARDS following cardiac surgery ranges from 0.4 to 8.1% ( 17 , 28 , 36 ). Daryl et al reported a 2.6% (113/4,366) incidence of ALI and ARDS in patients undergoing high-risk surgery, and 3.3% and 22% for patients undergoing spine surgery and high-risk vascular surgery, respectively ( 17 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, ARDS has been reported in 0.4%-8.1% of patients after cardiac surgery, which is associated with increased in-hospital mortality and hospital costs. 9,10 Of the 1011 patients included in the present study, a total of 53 patients suffered ARDS episodes within 7 days after surgery. The incidence of postoperative ARDS was 5.24%, which is consistent with that reported in previous literature.…”
Section: Discussionmentioning
confidence: 99%
“…Commonly used parameter to grade the severity of pediatric ARDS is oxygenation index [OI, OI = (FiO 2 × Paw × 100)/PaO 2 ] ( 24 , 25 ). In recent years, improvement in CPB technology has increased the safety of surgery for congenital heart diseases; still, postoperative ARDS remains a life-threatening complication after cardiac surgery in children ( 26 28 ). According to domestic and international research, incidence of ARDS in pediatric intensive care unit is 1–4%, and the mortality rate is as high as 22–65% ( 29 ).…”
Section: Discussionmentioning
confidence: 99%